Lanthanide Luminescence Revealing the Phase Composition in Hydrating Cementitious Systems. Issue 12 (13th December 2019) - Burek, Katja; Dengler, Joachim; Emmerling, Franziska; Feldmann, Ines; Kumke, Michael U.; Stroh, Julia
Abstract: The hydration process of Portland cement in a cementitious system is crucial for development of the high‐quality cement‐based construction material. Complementary experiments of X‐ray diffraction analysis (XRD), scanning electron microscopy (SEM) and time‐resolved laser fluorescence spectroscopy (TRLFS) using europium (Eu(III)) as an optical probe are used to analyse the hydration process of two cement systems in the absence and presence of different organic admixtures. We show that different analysed admixtures and the used sulphate carriers in each cement system have a significant influence on the hydration process, namely on the time‐dependence in the formation of different hydrate phases of cement. Moreover, the effect of a particular admixture is related to the type of sulphate carrier used. The quantitative information on the amounts of the crystalline cement paste components is accessible via XRD analysis. Distinctly different morphologies of ettringite and calcium−silicate−hydrates (C−S−H) determined by SEM allow visual conclusions about formation of these phases at particular ageing times. The TRLFS data provides information about the admixture influence on the course of the silicate reaction. The dip in the dependence of the luminescence decay times on the hydration time indicates the change in the structure of C−S−H in the early hydration period. Complementary information from XRD, SEM and TRLFS provides detailed information on distinct periods of the cement hydration process. Abstract : The hydration process of cement was investigated using X‐ray diffraction analysis, scanning electron microscopy, and time‐resolved laser fluorescence spectroscopy as complementary experimental techniques in the absence and presence of different organic admixtures. Our data showed that the different analysed admixtures and the used sulphate carriers have a significant influence on the hydration process, namely on the time‐dependence in the formation of different hydrate phases in cement.